Knockdown of two ER stress-related genes and their effect on pancreatic beta-cell function - Tan, Patricia Yan Dan (2018)
ER stress is associated with beta-cell dysfunction in Type 2 diabetes (T2D). A recent study by Dorajoo and colleagues show that several ER stress implicated genes including HSP90B1, DNAJC3, UCHL1 are upregulated in pancreatic islets from Singaporean-Chinese donors. Besides these genes, OLMALINC, a lincRNA with unknown function in beta-cells, was upregulated. We thus explored the effect of OLMALINC knockdown (KD) on expression of ER stress-related and beta-cell signature genes, under both normal and ER stress conditions. A second gene, ERO1β, shown to be important in mediating ER stress responses and beta-cell function in murine cell lines and mouse models, was also studied in the context of human beta-cells under normal and ER stress conditions. Our results show that OLMALINC KD had no significant impact on either beta-cell function or beta-cell responsiveness to heightened ER stress, suggesting that OLMALINC does not play a role in ER stress or significantly impact beta-cell identity and function. In contrast, ERO1β KD induced critical ER stress-related gene expression under ER stress conditions, corroborating murine models that ERO1β significantly impacted beta-cells responsiveness to ER stress. However, this effect was not seen in normal, nonER stress conditions. Our results propose that ERO1β downregulation in beta-cells may exacerbate ER stress, promote beta-cell dysfunction and thereby drive T2D pathogenesis.